Children can accurately recognize facial emotions from emoticons. (November 2017) - Oleszkiewicz, Anna; Frackowiak, Tomasz; Sorokowska, Agnieszka; Sorokowski, Piotr
Abstract: Developmental studies on children's ability to recognize emotions have focused on communication in physical, but not virtual space. Emotion recognition in real life is based on observation of facial expression whereas in virtual communication emotions are expressed with simple graphics named emoticons. To examine whether children can accurately identify emotions depicted with emoticons, we asked 68 children (4–8 years; 33 girls; no social media or smart phone experience) to indicate what emotions are expressed in photos of faces or emoticons. Our results indicate that children are able to accurately assign emotions from both photographs and emoticons, and that this ability develops earlier in girls than boys. The origins of accurate emotion recognition in virtual communication, as well as children's readiness to use virtual communication, are discussed. Highlights: Children (4–8 years) accuracy in emotion recognition from emoticons was tested. Sixty-eight children assigned emotions to pictures and emoticons. Pictures and graphical emoticons were more informative than typographical emoticons. Happiness and sadness were easiest to recognize, as opposed to disgust and fear. Accuracy was higher in girls and older children.